"With a little help from my friends" - The role of microbiota in thyroid hormone metabolism and enterohepatic recycling. (15th December 2017) - Virili, Camilla; Centanni, Marco
Abstract: The gut microbiota is composed of over 1200 species of anaerobes and aerobes bacteria along with bacteriophages, viruses and fungal species. Increasing evidence indicates that the intestinal microbiota, beside digestive equilibrium, is also crucial for immunologic, hormonal and metabolic homeostasis. The intestinal microbiota interacts with distant organs by signals which may be part of the bacteria themselves or their metabolites. Dysbiosis has been observed in inflammatory or autoimmune disorders such as multiple sclerosis or type 1 diabetes as well as in obesity and type 2 diabetes. Functional thyroid disorders were associated with bacterial overgrowth and a different microbial composition. Although thyroid metabolism was apparently disregarded, the interference of microbiota on peripheral iodothyronine homeostasis is an intriguing issue. In this review we focused on the interactions of intestinal microbiota with thyroid-related micronutrients and with the metabolic steps of endogenous and exogenous iodothyronines. Graphical abstract: Highlights: Intestinal bacteria may compete with the host in the case of selenium shortage. The intestine may play a relevant role as reservoir of an exchanging pool of thyroid hormones. The metabolic pathways of iodothyronines more sensitive to microbiota seem to be deconjugation reactions. Microbiota may regulate thyroid homeostasis by metabolic enzymes or modulating iodothyronines bioavailability. Intestinal dysbiosis may represent an additional cause of thyroxine malabsorption.